Prove laws of logarithm?

Asked by simran2 | 5th Aug, 2010, 12:00: AM

Expert Answer:

logc (ab) = logc a + logc b
Proof: Let logc (ab) = d,  logc a = e,  logc b = f;
Hence, we can write, d = e + f            ... (1)
cd = ab and ce = a, cf = b              .. using logarithm definition,
 
Now ab = axb
cd = ce x cf
 
cd = ce+f
Which gives, d = e + f.
Similarly we can prove other laws.
Regards,
Team,
TopperLearning.

Answered by  | 5th Aug, 2010, 06:34: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.